HUBUNGAN ANTARA KESULITAN BELAJAR DENGAN PRESTASI BELAJAR SISWA KELAS IV SDN 11 SUMBAWA - Toto Subiantoro; Ivon Arisanti; Roni Hartono (Fakultas Psikologi dan Humaniora- Universitas Teknologi Sumbawa, 2019)
This study aim to determine the relationship between learning difficulties and learning achievement of fourth grade students of SDN 11 Sumbawa. This study used a descriptive quantitative approach. The research subject was taken using a population study approach with a total of 70 4th grade students of Sumbawa 11 Elementary School. The research data was obtained by using report and scale report value scoring instruments to scale using the scale of learning difficulties. Learning difficulty scale consist of 28 items with a validity coefficient between 0.310 to 0.794 and a reliability coefficient of 0.739. The results of this study indicate that there is a significant relationship between Learning Difficulties and Learning Achievement correlation coefficient value (rxy) of 0.419 with p count = 0.0001 / p<0.05. Based on the average calculation in general, based on the results of the study the relationship between learning difficulties and learning achievement was in the medium category. Based on the results of calculations for data obtained from the scale of Learning Difficulties, from 70 subjects there were 8 subjects (11.4%) in the very high category, 6 subjects (8.6%) in the high category, 34 subjects (48.6 %) were in the medium category, 21 subjects (30%) were in the low category, and 1 subject (1.4%) were in the very low category. While the results of calculations for the data obtained from Learning Achievement of 70 subjects found 3 subjects (4.3%) were in the very high category, 14 subjects (20%) were in the high category, 36 subjects (51.4%) were in the category moderate, 15 subjects (21.4%) were in the low category, and 2 subjects (2.9%) were in the very low category.